Environmental, social and governance adoption in the Malaysian wood products and furniture industries: awareness, adoption and challenges - Ratnasingam, Jegatheswaran; Ab Latib, Hazirah; Choon Liat, Lim; Jegatheswaran, Natkuncaran; Othman, Kamaruzaman; Amir, Mohd Afthar (North Carolina State University, 2023)
As the world intensifies efforts to mitigate the effect of global climate change, an on-line survey was carried out involving 1,081 wood products and furniture manufacturers in Malaysia. The main objective was to evaluate the level of awareness, extent of adoption, and challenges faced by these manufacturers in adopting environmental, social, and governance (ESG) practices. The survey found that large-sized companies were more receptive to adopting ESG practices, as opposed to the medium-, small-, and micro-sized companies. Respondents were apparently more responsive to environmental requirements, followed by governance, and finally the social factors. Within the environmental sphere, compliance with using certified and legal wood and wood products, waste management, and conformance to emission standards were well received among respondents. The survey revealed that market forces and legislative requirements were the two most important factors that enticed respondents to comply with the ESG practices; among those respondents who did not comply with ESG requirements, the primary deterrent factors include lack of awareness, no direct benefit from adopting ESG, and the high cost involved. The ESG compliance may transform the wood products and furniture industries into a more sustainable industry, offering equitable wages and green jobs while producing high value-added products.